2020
DOI: 10.1038/s41594-020-0511-8
|View full text |Cite|
|
Sign up to set email alerts
|

SARS-CoV-2 Nsp1 binds the ribosomal mRNA channel to inhibit translation

Abstract: ARS-CoV-2 is the causing agent of the COVID-19 pandemic and belongs to the genus of beta-coronaviruses, with enveloped, positive sense and single-stranded genomic RNA 1. On entering host cells, the viral genomic RNA is translated by the cellular protein synthesis machinery to produce a set of non-structural proteins (NSPs) 2. NSPs render the cellular conditions favorable for viral infection and viral mRNA synthesis 3. Coronaviruses have evolved specialized mechanisms to hijack the host gene expression machiner… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
463
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(484 citation statements)
references
References 42 publications
20
463
0
1
Order By: Relevance
“…In all these distinct intermediates, Nsp1 was found to bind in the position and conformation to that observed in the in vitro complex, confirming its role as inhibitor of translation initiation (Thoms et al, 2020). These findings were confirmed in an independently resolved structure of Nsp1 in complex with several ribosomal components (Schubert et al, 2020).…”
Section: Nsp1 Nsp2 Nsp5supporting
confidence: 58%
See 1 more Smart Citation
“…In all these distinct intermediates, Nsp1 was found to bind in the position and conformation to that observed in the in vitro complex, confirming its role as inhibitor of translation initiation (Thoms et al, 2020). These findings were confirmed in an independently resolved structure of Nsp1 in complex with several ribosomal components (Schubert et al, 2020).…”
Section: Nsp1 Nsp2 Nsp5supporting
confidence: 58%
“…Recent studies have confirmed that Nsp1 from SARS-CoV-2 plays the same roles as its counterpart in SARS-CoV during virus infection (Schubert et al, 2020;Thoms et al, 2020). In the study by Thoms et al (2020) a complex between purified Nsp1 and 40S ribosomal subunits was reconstituted in vitro by cryo-EM.…”
Section: Nsp1 Nsp2 Nsp5mentioning
confidence: 96%
“…Papain-like protease 137 PLpro (ORF 1a, Nsp3 138 ), cleaves 139 proteinaceous post-translational (ref 131) modifications on host proteins to evade host anti-viral immune responses. Nsp1 140 suppresses host translation by cleaving cell mRNAs 141 and competes 142 with mRNAs for binding to human 40S ribosomal mRNA channel 143 (as well as 43S, 80S subunits). Type 1 144 interferon 145 (IFN-1) response 146 is modulated by Nsp1, Nsp 6 and Nsp13, which interferes indirectly with IFN-1 by suppressing the phosphorylation and/or nuclear translocation of other cellular molecules 147 involved in catalyzing the IFN-1 response.…”
Section: Array Of Targetsmentioning
confidence: 99%
“…Papain-like protease 137 PLpro (ORF 1a, Nsp3 138 ), cleaves 139 proteinaceous post-translational (ref 131) modifications on host proteins to evade host anti-viral immune responses. Nsp1 140 suppresses host translation by cleaving cell mRNAs 141 and competes 142 with mRNAs for binding to human 40S ribosomal mRNA channel 143 (as well as 43S, 80S subunits). Type 1 144 interferon 145 (IFN-1) response 146 is modulated by Nsp1, Nsp 6 and Nsp13, which interferes indirectly with IFN-1 by suppressing the phosphorylation and/or nuclear translocation of other cellular molecules 147 involved in catalyzing the IFN-1 response.…”
Section: Array Of Targetsmentioning
confidence: 99%